Cross-Slabs in the Isle of Man brought to light since December 1915 - Kermode, P M C (Proceedings of the Society of Antiquaries of Scotland, 1921)
Recent discoveries come from the parishes of Jurby, German and Braddan and include plain incised crosses along with two of Celtic design.